Research and the Christian identity of universities - Ana Marta González (Church, Communication and Culture)
In order to explore the relationship between research and universities with a Christian identity, it is important to be clear about the identity of social realities and the meaning of ‘Christian identity’ when applied to universities. In my view, the latter requires three elements: (1) assigning a central role to theological reflection, (2) recognizing a mediating role to philosophy, and (3) encouraging a reflective posture in all disciplines. These three aspects should be considered and secured through adequate research policies that manage external constraints with internal ones.